"Sharpening Your Mind, Strengthening Your Body" Parental Perceptions on the Use of Strength and Conditioning in Children and Youth - Michael Joseph Duncan; Ricardo Manuel Gonçalves Martins; Emma Lisa Jane Eyre (MDPI AG, 2022)
Although strength and conditioning is beneficial and safe for children to engage in there remain myths and misconceptions form parents regarding its use which prevent its widespread take up. This study explored parents' attitudes and beliefs about strength and conditioning in their children. Thirty-one parents (21 dads, 10 mums) took part in one of four focus groups exploring the topic. Thematic analysis was used resulting in themes and sub themes centred on: Beliefs; Determinants; Coach Education; Coach Communication; and Relationship to the Game. There were also smaller aspects of the focus groups which touched upon autonomy as a concept related to implementation of strength and conditioning specifically. Overall, parents of children who play grassroots sport hold generally positive perceptions on use of strength and conditioning with their children, considering it beneficial for both physical and mental development. Key factors relating to successful implementation of strength and conditioning for children focus on having a qualified coach in that particular area (rather than a generic sports coach), effective communication between coach and parents, and coach and children in terms of the benefits of engaging with strength and conditioning.